Preliminary Phytochemistry and Antioxidant Activities of the Ethanol Extract of Ficus abutilifolia Leaves - Attama, Chika; Lawrence, Luka; Chidama, Ndakudu Bulama (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2025)
Medicinal plants harbor bioactive compounds utilized for addressing various health challenges. This current research focuses on the study of Ficus abutilifolia, collected from Askira Uba, Borno State, Nigeria. Ethanol was employed to extract compounds from the plant leaves. The extracts underwent qualitative phytochemical screening using established procedures. The screening identified the presence of Alkaloids, Saponins, Tannins, Anthraquinones, Steroids, Glycosides, Flavonoids, reducing sugar, amino acids, and terpenoids, while Phytosterol was notably absent. The antioxidant activity of the crude extracts was assessed using two complementary test systems: 2,2-diphenyl-1-picrylhydrazyl (DPPH) and hydrogen peroxide free-radical scavenging assays, with Ascorbic acid serving as the standard. The free radical scavenging activity of the leaf crude extracts at different concentrations (2.5, 5, 7.5, and 10 µl/mL) demonstrated a concentration-dependent increase. In the DPPH method, the crude extract at a concentration of 10 ?g/mL exhibited 58.2 % antioxidant activity. Similarly, in the hydrogen peroxide radical scavenging assay, it was observed that at a concentration of 10 ?g/mL, the crude extract demonstrated an inhibition of 72.7 %. In conclusion, the ethanol extract from the plant exhibited potent inhibition of free radicals, possibly attributed to the presence of secondary metabolites.